Optimal time for constant drug infusion initialization in neuromuscular blockade control - Angela Miranda (2014)
This paper presents a control strategy for neuromuscular blockade (NMB) level, in order to determine the optimal time to initialize the administration of the muscle relaxant rocuronium by means of the continuous infusion of a constant dose. The constant value of muscle relaxant for a particular patient undergoing general anesthesia is computed in order to guarantee that the steady-state value of neuromuscular blockade level is the desired reference value. In order to apply this open-loop control strategy, the patient's NMB response to rocuronium is assumed to be modeled by a recently proposed parameter parsimonious model.